A Micro Mid‐Infrared Spectroscopic Study of Chang'e‐5 Sample. Issue 8 (24th August 2022) - Yang, Yazhou; Jiang, Te; Liu, Yang; Xu, Yuchen; Zhang, Hao; Tian, Heng‐Ci; Yang, Wei; Zou, Yongliao
Abstract: The Chang'e‐5 (CE‐5) mission has successfully returned samples from a site that is much younger than the sites of all previous lunar sampling missions. Sample analysis results reported so far have revealed a more complex sampling area than previously thought, casting uncertainties over the interpretation of remote sensing spectral data and the U and Th abundance derived from the orbital data. Laboratory spectral measurement of the returned samples can serve as validation of remote sensing observations and thus help refine our understanding of the geological evolution of the landing region. In this study we report detailed micro mid‐infrared (MIR) spectral characteristics of individual soil grains of CE‐5 samples. The spectral analysis results show that the CE‐5 olivine grains have low Fo (molar Mg/[Mg + Fe] × 100) consistent with previous studies, indicating a Fe‐rich source region of the mantle or a highly evolved magma. These olivine grains show high level of crystallinity, implying low degree of space weathering. Most of the CE‐5 glasses analyzed are spectrally consistent with mare impact glasses, despite that a few of them may have a volcanic origin. These laboratory spectral analysis of CE‐5 samples in the MIR wavelengths at a micro scale, together with the derived MIR optical constants of the olivine, pyroxene, plagioclase, and glass grains, provide important input for the modeling and interpretation of thermal remote sensing data of the Moon. Plain Language Summary: The Chang'e‐5 (CE‐5) mission successfully landed in the north‐west of the Moon's nearside, and it returned samples that are quite different from previous returned samples. To study the compositions and possible origins of the samples, we performed a detailed micro mid‐infrared spectral analysis on individual mineral and glass grains. The ratio of Mg/(Mg + Fe), also called Fo, is often used to differentiate the magma source where the mineral formed. Our analysis results show that the CE‐5 olivine grains have low Fo values than previously returned olivine samples, indicating that its source region is rich in Fe. The CE‐5 olivine grains also have high level of crystallinity, implying they have not been exposed long enough to be deformed. We also found that most of the glass beads analyzed likely originated from impact within the maria region. Using remote sensing techniques like hyperspectral imaging, we can obtain composition information for a large‐scale region. Laboratory spectral analysis of returned samples can provide important ground‐truth for interpretations of remote sensing data. To build a link between returned sample and orbital spectral data, we derived the refractive index for typical mineral and glass samples, which will benefit the analysis of orbital spectral data. Key Points: Micro mid‐infrared spectral measurements were performed and optical constants were derived for typical Chang'e‐5 (CE‐5) soil grains The CE‐5 olivine grains have low Fo values, indicating a Fe‐rich source region or a highly evolved magma Most of the CE‐5 glasses analyzed are likely attributed to mare impact group, despite a few others may have a volcanic origin